2016
DOI: 10.1164/rccm.201512-2494oc
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Outpatient Treatment Based on the Hestia Clinical Decision Rule with or without N-Terminal Pro–Brain Natriuretic Peptide Testing in Patients with Acute Pulmonary Embolism. A Randomized Clinical Trial

Abstract: Outpatient treatment of patients with PE selected on the basis of the Hestia criteria alone was associated with a low risk of adverse events. Given the low number of patients with elevated NT-proBNP levels, this trial was unable to draw definite conclusions regarding the incremental value of NT-proBNP testing in patients who fulfill the Hestia criteria. Clinical trial registered with www.trialregister.nl/trialreg/admin/rctview.asp?TC=2603 (NTR2603).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 26 publications
4
57
1
5
Order By: Relevance
“…In a subsequent non-inferiority trial that randomized 550 patients to direct discharge based on the Hestia criteria alone versus additional NT-proBNP testing and discharge if levels were ⩽500 pg/mL, the primary outcome (30 day PE-or bleeding-related mortality, cardiopulmonary resuscitation, or admission to an intensive care unit) was very low in both arms. The results suggest no incremental value of natriuretic-peptide testing in patients who are eligible for home treatment based on the Hestia criteria, although the study was not powered to exclude this possibility [318].…”
Section: Management Of Low-risk Pulmonary Embolism: Triage For Early mentioning
confidence: 93%
See 1 more Smart Citation
“…In a subsequent non-inferiority trial that randomized 550 patients to direct discharge based on the Hestia criteria alone versus additional NT-proBNP testing and discharge if levels were ⩽500 pg/mL, the primary outcome (30 day PE-or bleeding-related mortality, cardiopulmonary resuscitation, or admission to an intensive care unit) was very low in both arms. The results suggest no incremental value of natriuretic-peptide testing in patients who are eligible for home treatment based on the Hestia criteria, although the study was not powered to exclude this possibility [318].…”
Section: Management Of Low-risk Pulmonary Embolism: Triage For Early mentioning
confidence: 93%
“…Carefully selected patients with low-risk PE should be considered for early discharge and continuation of treatment at home, if proper outpatient care and anticoagulant treatment can be provided c [178,206,[317][318][319].…”
Section: Recommendations Class a Level Bmentioning
confidence: 99%
“…Elevated levels of both BNP and NT-proBNP were associated with worse outcomes (combined 30-day mortality OR 7.6 (3.4–17)). In a more recent study, patients who met the Hestia criteria for OP management of PE were randomised to direct discharge or NT-proBNP testing; those with elevated NT-proBNP were admitted for IP management 31 . The study confirmed that patients meeting the Hestia criteria had low rates of adverse outcomes and failed to show an additional benefit of NT-proBNP testing, possibly due to low numbers of patients with elevated NT-proBNP levels.…”
Section: Imaging Laboratory and Other Clinical Investigations For Rimentioning
confidence: 96%
“…This definition does not address tissue oxygenation. [23][24][25][26][27] Hestia may therefore be a good alternative for sPESI. 15 However, PaO 2 is important because oxygen sensing systems respond to changes in PaO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In Hestia, oxygen supplementation to maintain a saturation above 90% is an exclusion criterion for outpatient treatment, which means that patients with a saturation of 91% at room air can be treated as outpatients if other criteria are also met. [23][24][25][26][27] Hestia may therefore be a good alternative for sPESI.…”
Section: Discussionmentioning
confidence: 99%